Non-destructive estimation of oil palm yield and quality with fluorescence sensing - Abu Kassim, Norul Husna (2016)
Fluorescence sensing is one of the proximal sensor techniques which use instruments operating very close to or in contact with the object of inquiry. It is an emerging approach in assessing and monitoring crop yield and quality. At present, ineffective Fresh Fruit Bunch (FFB) maturity assessment and untimely harvesting are problematic to the Malaysian oil palm industry. The current method of FFB assessment is extremely tedious and a time-consuming process that is destructive, prone to errors and inconsistent. Thus, implementation of an oil palm harvesting protocol that deploys a nondestructive sensor-based approach to assess FFB ripening is highly desirable. The objectives of this study were: i) to quantify the relationship between palm oil quality (DOBI) and fluorescence-sensed anthocyanin and flavonol contents across different palm ages, ii) to quantify the relationship between palm oil yield (OER) and fluorescence-sensed anthocyanin and flavonol contents across different palm ages, and iii) to identify the best-fitted model and validate the spatial distribution of palm oil quality, yield and fluorescence-sensed anthocyanin and flavonol contents across different palm ages. In this study, three 2-ha plots were demarcated based on different year of planting; 2002 (12 year old palms), 2005 (9 year old palms) and 2008 (6 year old palms). Sixty FFBs and their corresponding loose fruits were scanned for each plots using fluorescence sensor (Multiplex®). Overall, secondary metabolites such as anthocyanin and flavonol are proven to be a reliable indicator of palm oil quality and yield (r=0.6 of anthocyanin and r=0.8 of flavonol). However, fluorescence indices (Anth_B, Flav_B and NBI) show mixed correlation strengths with DOBI and OER across different palm ages. For the first objective, the secondary metabolites; anthocyanin and flavonol, were analysed to determine the relationship between Deterioration of Bleacheability Index (DOBI) and secondary metabolites content. Results showed that the estimated strength of secondary metabolites was more pronounced toward oil quality in 6 and 9 year old palms (younger palms). For the second objective, the secondary were analyzed to determine the relationship between Oil Extraction Rate (OER) and secondary metabolites content. Results showed that the estimated strength of secondary metabolites was more pronounced toward oil yield in 9 and 12 year old palms (older palms). As a conclusion, both palm oil quality and oil yield determinations using fluorescence indices are most applicable in matured 9 year palms (r=0.63 and 0.52 with DOBI; r=0.65 and 0.53 with OER, respectively). This indicates that palm oil quality and yield, particularly of 9 year old palms, are highly related to fluctuations in anthocyanin and flavonol contents in the fruit. According to Corley and Tinker 2003, oil palm has reached its maturity and their growth becomes more stable at 9-10 years after planting which is when their productivity is at its maximum. This could also infer that anthocyanin and flavonol contents in the 6 and 12 year old palms are more indicative of their metabolic process rather than their oil quality or oil yield. This observation is in agreement with Muller et al. (2013) who reported that during plant growth (particularly in 6 and 12 year palms), higher accumulation of anthocyanin and flavonol contents will act as a trade-off between the plant’s primary and secondary metabolic system, which are not stable as compared in 9 year old palms. For the third objective, ten variables of spatial distribution of palm oil quality, palm oil yield and fluorescence-sensed secondary metabolites were modeled and validated for each age group. Majority of variables for all three age groups have a short effective range (<153 m) with a strong spatial dependence (>99.7%) except for OER of 2008. Most of the tested variables could be had 99% variability that is explainable. Across different age groups, TFC was recorded with lowest R2 values ranging between 0.03-0.07 which due to secondary metabolism of flavonoid in palm oil meanwhile majority of the variables showing a moderate R2 with value ranging between 0.5-0.7 (Anth_B, Flav_B, Anth_Lf, Flav_Lf and TAC). CV values of variables in all age groups can be divided into two groups; low and moderate variability (CV=7-49% in 2002; 13-41% in 2005; and 7.7-37.8% and 52.7-73.4% in 2008, respectively). This indicates that all variables are greatly being influenced and significantly associated with secondary metabolite concentrations in oil palm compared to spatial regularity. Fluorescence sensor has a promising potential in determining secondary metabolites in oil palm, however more research and future findings are needed to support and compliment this work.